Maggot cultivation as an organic waste decomposer at the SahabatQu Islamic Boarding School - Fitria Sulistyowati; Nurcholish Arifin Handoyono; Sony Yunior Erlangga; Anisa Putri Damayanti; Arif Setiawan (Community Empowerment, 2023)
In the strategic plan of the DIY Environmental Service (DLH), it is emphasized that to reduce waste accumulation in TPSTs, waste sorting at the upstream level, such as households, is crucial. However, the issue persists at this level, as observed in boarding school-based institutions like the SahabatQu Islamic Boarding School in Sleman Regency, DIY. The negative repercussions of this problem include a decline in the quality of life and health among students. This service initiative aims to enhance the skills of students by cultivating maggots using organic waste sorted from the school's waste. The approach involves socialization, practical training, and mentoring. The outcome of this activity is an improvement in the knowledge and skills of SahabatQu Islamic Boarding School students in raising maggots to the pre-pupae stage, with some successfully reaching the phase of becoming BSF flies and entering the mating process.